Hydrogen generation by soluble CO reaction with zero-valent iron or scrap iron and the role of weak acids for controlling FeCO formation - Constantinou, Despina; Samanides, Charis G.; Koutsokeras, Loukas E.; Constantinides, Georgios; Vyrides, Ioannis (My University, 2023)
This study points out a new perspective on CO2 sequestration and H2 gas generation in a system of either zero-valent iron (Fe0) or scrap iron along with NaHCO3 and citric acid. Under a high bicarbonate environment, micro-size Fe0 (5–40 g/L) is oxidized at mild anaerobic conditions, generating hydrogen gas with a production rate in the range of 0.09–0.55 g(H2)/kg(Fe0)·h. At the same conditions without bicarbonate, the generation of H2 was negligible. At the end of the reaction, the pH was alkaline so it can be used to absorb CO2. Carbonate ions create a passivation layer on the Fe0 surface, called siderite (FeCO3), that entrapped Fe0 and hindered H2 production. By comparing citric, oxalic, and ascorbic acids for their ability to remove the siderite layer, citric acid was found to be the most effective. In a system of scrap iron-NaHCO3/citric acid, for seven consecutive cycles, it was found that by replacing the media solution with a new media after the end of each cycle and flushing with CO2 in the beginning of each cycle resulted in higher than 85 vol% H2 after one day of exposure and higher than 94 vol% H2 at the end of each cycle.
Keywords: CO2 utilization; Fe-ligand; Hydrogen production; Siderite; Scrap iron